THE PERFORMANCE OF LAYING HENS FED DIFFERENT CALCIUM SOURCE - Kismiati, S.; Yuwanta, T.; Zuprizal, Z.; Supadmo, S. (Diponegoro University, 2012)
The research was aimed to evaluate the performance of laying hens fed different calcium sources.Two hundreds of Isa Brown laying hens were used in this study. The hens were raised in individualbattery cages units for 12 weeks. Four calcium source (limestone as a control, 5% limestone + 2.5%eggshells waste, 2.5% limestone + 5% eggshells waste and 7.5% eggshell waste) were used in feedexperiment. A completely randomized design was applied, with 4 treatments and 5 replications. Eachexperimental unit consisted of 10 laying hens. The parameters measured were feed intake, proteinintake, calcium intake, phosphorus intake, egg production, egg weight and feed conversion ratio. Resultsof the research showed that the calcium source had significantly effect on performance productions. Theuse of eggshell waste 7.5% significantly increased the feed intake, calcium intake, phosphorus intake,egg production and egg weight except for feed conversion ratio. The conclusion of this research was thatthe use of eggshell waste as calcium source of feed resulted in better performance than using limestoneor mixed limestone with eggshell waste.